1967
DOI: 10.1190/1.1439885
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Regime of a Large Diameter Borehole: Instability of the Water Column and Comparison of Air‐ and Water‐filled Conditions

Abstract: Temperatures were measured as a function time and depth in a borehole before and after it had been filled with water. The hole is 25 cm in diameter, 340 m deep, and effectively sealed from influx of ground water. The measurements reveal that: (1) Temperature differences between the air‐filled hole and the water‐filled hole (after dissipation of the water injection disturbance) do not exceed 0.05°C at the same depth. (2) Temperatures in the water‐filled hole exhibit oscillations at all depths where temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 0 publications
1
33
1
1
Order By: Relevance
“…This value of geothermal gradient is clearly surpassed by several orders of magnitude everywhere in Hole 504B. According to Diment (1967), small-diameter (2-3 cm) holes are usually stable, larger ones (6-8 cm) approach instability, and large-diameter wells (> 10 cm) are typically unstable. Thus, according to these criteria, convective fluid movement is likely to occur throughout the water column in Hole 504B.…”
Section: Convection Within the Boreholementioning
confidence: 99%
“…This value of geothermal gradient is clearly surpassed by several orders of magnitude everywhere in Hole 504B. According to Diment (1967), small-diameter (2-3 cm) holes are usually stable, larger ones (6-8 cm) approach instability, and large-diameter wells (> 10 cm) are typically unstable. Thus, according to these criteria, convective fluid movement is likely to occur throughout the water column in Hole 504B.…”
Section: Convection Within the Boreholementioning
confidence: 99%
“…3). These small drifts in temperature may represent instances of transient fl uid exchange between the borehole and the formation (e.g., Drury et al, 1984;Ge, 1998;Šafanda et al, 2007) or localized intervals of fl uid convection within the borehole (e.g., Diment, 1967;Fisher and Becker, 1991). Substantial thermal anomalies appear at 647 mbsf, a consequence of circulation loss and drilling fl uid entering the surrounding formation within a fracture zone delineated by a thin lava fl ow (Falconer et al, 2007;Krissek et al, 2007).…”
Section: Temperature Logs and Geothermal Gradientmentioning
confidence: 99%
“…Using this equation, it can be shown that for normal geothermal gradients (approximately 25 °C/km), convection can be expected in boreholes with diameters greater than about 5 cm. However, several field investigations by Urban et al (1978), Diment (1967), Gretener (1967), and Wisian et al (1998), as well as the observations by this author, have shown that although convection cells do form, they rarely extend vertically more than a few borehole diameters before dying out. Thus, the general effect of convection within boreholes is to decrease the signal-to-noise ratio of a temperature log without interfering with broader temperature trends.…”
Section: Thermal Gradientmentioning
confidence: 63%
“…Since, generally, borehole temperatures increase with depth, it would appear that the warmer waters deeper within the borehole would tend to rise up through the cooler fluids higher in the borehole, producing convection cells. Hales (1937), Auld (1948), and Diment (1967) investigated this phenomenon and developed, and refined, an equation to describe convection in boreholes relating fluid properties and the radius of the borehole to a critical thermal gradient, above which convection would be expected. Using this equation, it can be shown that for normal geothermal gradients (approximately 25 °C/km), convection can be expected in boreholes with diameters greater than about 5 cm.…”
Section: Thermal Gradientmentioning
confidence: 99%